Dynamics of Agricultural Information and Effect on Income of Melon Farmers in Enugu-Ezike Agricultural Zone of Enugu State, Nigeria. Issue 1 (2nd January 2016) - Iwuchukwu, Juliana Chinasa; Ekeh, George Okechukwu; Madukwe, Michael C.
ABSTRACT: The study assessed effects of agricultural information on the income of melon farmers. Ninety melon farmers constituted the sample for the study. Data were collected through an interview average annual income of the respondents from melon only was ₦7, 455.4, while their total average schedule, while percentage mean score and correlation were used in the analysis. Findings reveal that the monthly income was ₦1, 223. About 62 and 42% of the respondents, respectively, did not receive information on melon production and general agriculture. Thus, a positive and significant relationship exists between the number of times respondents received information on melon/general agriculture and their incomes.